Molecular and palaeoecological evidence for multiple glacial refugia for evergreen oaks on the Iberian Peninsula - López de Heredia, U.; Carrión, J. S.; JIMÉNEZ, P.; COLLADA, C.; Gil, L. (Journal of Biogeography, 2007)
Aim A multiple glacial refugia hypothesis for Mediterranean plant species was tested with the evergreen Quercus complex (Quercus suber L., Quercus ilex L. and Quercus coccifera L.) from the Iberian Peninsula, using molecular and palaeobotanical data. Location The Iberian Peninsula, which is an ecologically and physiographically complex area located on the western edge of the Mediterranean Basin. Methods We sampled 1522 individuals from 164 populations of Q. suber, Q. ilex and Q. coccifera. A review of the recent literature on fossil pollen and charcoal records and a nested clade analysis on chloroplast DNA polymerase chain reaction-restriction fragment length polymorphism was carried out to infer demographic and historical processes. Results The analysis indicates at least one glacial refugium for Q. suber in southwestern Iberia. Extensive introgression of Q. suber with Q. ilex indicates several potential refugia in eastern Iberia. Past fragmentation was followed by a restricted range ﬂow/range expansion, suggesting multiple refugia for Q. ilex–Q. coccifera elsewhere in central and northern Iberia and multiple areas of secondary contact. This ﬁnding is consistent with fossil records. Main conclusions The predicted multiple refugia during glacial periods indicates the existence of secondary post-glaciation contact areas. These areas contained complex diversity patterns resulting mainly from range expansions followed by isolation by distance. To a lesser degree, traces of restricted and longdistance dispersal were also found.
Keywords: cpDNA PCR-RFLPs; evergreen Quercus; fossil pollen; glacial refugia; iberian peninsula; introgression; nested clade analysis; oaks; phylogeography

Patterns and processes of Late Quaternary environmental change in a montane region of southwestern Europe - Carrión, J. S. (Quaternary Science Reviews, 2002)
This paper examines the Late Quaternary (c. 20,300–o505 cal yr BP) environmental history of Siles, a lake situated at 1320 m in the Segura mountains of southern Spain, with the goalof establishing the mechanisms exerting controlon vegetation change. Palaeoecological indicators include pollen, microcharcoal, spores of terrestrial plants, fungi, and non-siliceous algae, and other microfossils. The Siles sequence is shown to be sensitive to climatic change, although the control exerted by climate on vegetation is ultimately shaped by disturbances and species interactions, determining the occurrence of century-scale lags and threshold responses. Biotically induced changes of vegetation are also shown at the intrazonal level of variation. The new sequence is placed in the context of two previous records to postulate a picture of Holocene environmental change for the Segura region. The existence of mid-elevation glacial refugia for a number of temperate and Mediterranean trees is shown. A mid-Holocene phase (c. 7500– 5200 cal yr BP) emerges regionally as the time of maximum forest development and highest lake levels. The early Holocene occurs as a generally dry, pyrophytic period of pine forests, with grassland scrub in high altitudes, and the late Holocene as a period of protracted vegetation sensitivity, with return to development of pine forests, spread of xerophytic communities, and increased ﬁre activity, under the context of dry spells, localized anthropogenic disturbance, and shallowing and desiccation of lakes. Several events described here correlate with established times of abrupt transitions in the climates of northern Europe, the Mediterranean basin, north Africa, and the Sahel
Keywords: Holocene; Mediterranean (voyant); Pollen analysis; vegetation belts

Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach - Carrión, J. S.; Parra, I.; Navarro, C.; Munuera, M. (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species
Keywords: Cork oak; historical biogeography; iberian peninsula; palaeoecology; pollen.

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J. S.; Geel, B. Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas